Вплив та екологічна оцінка рівня шкідливих речовин відпрацьованих газів дизельних двигунів в залежності від режимів роботи МТА - Мітков, Василь Борисович; Митков, Василий Борисович; Mitkov, Vasyl (Мелітополь: ТДАТУ, 2017)
UK: При експлуатації МТА в результаті зниження технічного стану двигунів збільшується рівень шкідливих викидів у ВГ. На рівень шкідливих викидів впливає не тільки технічний стан двигуна, а також швидкісний та навантажувальний режим роботи дизеля. Характер зміни викидів СО, СН, NOx в залежності від ступені завантаження трактора та частоти обертання колінчастого валу дизеля. EN: Comprehensive approach to assessing the environmental safety of the machine and tractor units (MTU), which will assess impact on the environment as a predicted i-th ecological safety factor was worked out. Dependences which allow to determine the amount of harmful ex-haust emissions (NOx, CO, CH) depending on the level of loading of the tractor was developed. Us-ing the theoretical relationships were determined total number of harmful emissions (NOx, CO, CH) depending on engine power. To determine the modes of engine operation when volume of harmful substances emissions (NOx, CO, CH) reach maximum values has been developed depend-encies of harmful emissions, which are placed on the regulatory characteristic of the engine. The proposed method of determining the level of harmful exhaust emissions, depending on the diesel tractor engine mode HTZ-170 allows to use it for other brands of tractors for agricultural purposes in the assessment of environmental safety.
Keywords: екологічна оцінка; шкідливі речовини; дизельні двигуни; МТА; шкідливі викиди; навантажувальний режим роботи дизеля; energy vehicle; exhaust gases; environmental safety; agricultural unit; complex coefficient; theoretical dependence; harmful emissions